Correcting preoperative iron deficiency as part of patient blood management in the 'real world': results of an audit on an Australian cohort. (2nd February 2018) - Hong, F. S.; Sieradzki, N.; Pollock, C.; Nasra, F.; Churilov, L.; Mo, A.; Willcox, A.; Ho, W. K.; Smith, C.
Abstract : Background: The perioperative module of the Australian Patient Blood Management guidelines recommended preoperative iron therapy for surgical patients with, or at risk of, iron deficiency anaemia. After implementing a preoperative haemoglobin optimization programme in our institution, an audit was undertaken to evaluate the benefit of preoperative iron therapy in 'real world' clinical practice. Methods: Elective major surgery patients assessed in surgical pre‐admission clinics from 1 July 2013 to 30 June 2014 were screened for iron deficiency and anaemia. Those who were iron deficient (ferritin <30 μ g/l), regardless of haemoglobin level, received either daily oral iron supplementation until day of surgery or intravenous iron polymaltose 1 g preoperatively (intervention group). Control patients who were not iron deficient were matched to the intervention group using propensity scores based on age, sex and surgical unit. The primary end‐point was the proportion of patients requiring perioperative red cell transfusion in intervention and control groups. Results: One hundred and fourteen patients (8·75%) had iron deficiency. Ninety‐three patients received preoperative iron therapy, 17 (18·3%) of whom required red cell transfusions postoperatively. Of the 332 control patients, 71 (21·4%) required red cell transfusion. After adjusting for preoperative haemoglobin and time from screening to surgery, the odds of red cell transfusion were significantly lower in the intervention group compared to controls (odds ratio: 0·512, 95% confidence interval: 0·268–0·977; P = 0·04). Conclusion: Preoperative iron therapy was associated with reduced need for postoperative red blood cell transfusion in elective major surgery patients who were initially iron deficient.